2018
DOI: 10.26440/ihrj/02_05/190
|View full text |Cite
|
Sign up to set email alerts
|

Radiomorphometric Localization of Mental Foramen and Mandibular Canal using Cone Beam Computed Tomography as an Aid to Gender Determination- A Retrospective Study

Abstract: AIM: The present study aimed at evaluating the role of mental foramen and mandibular canal in gender determination using CBCT.METHODOLOGY: A total number of 73 volumes of CBCT of the mandible was evaluated. Four measurements were used to assess the bucco-lingual and supero-inferior location of mandibular canal and the supero-inferior location of mental foramen was determined using two measurements on both right and left sides of the mandible. Inter and intra-observer variability was analyzed with help of t-tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Our results are in agreement with Shams et al, 14 who found that it was 14.4 mm in males and 12.8 mm in females. Uppel et al, 15 also reported higher values in males compared to females.…”
Section: Discussionmentioning
confidence: 87%
“…Our results are in agreement with Shams et al, 14 who found that it was 14.4 mm in males and 12.8 mm in females. Uppel et al, 15 also reported higher values in males compared to females.…”
Section: Discussionmentioning
confidence: 87%